Assessment of Small Dense Low-Density Lipoprotein and Apolipoprotein B/Apolipoprotein A-I Ratio to Predict the Peripheral Arterial Disease in Patients with Hypertension - Kurniawan Prihutomo; MID. Pramudianti; Amiroh Kurniati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Small Dense Low-Density Lipoprotein (sdLDL) and the ApoB/ApoA-I ratio has greater atherogenic potential and is a better marker to predict atherosclerotic blood vessel disease. The purpose of this study was to determine the relationship between the sdLDL and ApoB/ApoA-I ratio to assess the prevalence risk of Peripheral Arterial Disease (PAD) in hypertensive patients. A cross-sectional observational analytic study was performed in 51 hypertension patients with age> 18 years old in Dr. Moewardi Hospital Surakarta from May until June 2018. Patients have measured ABI scores, BMI, blood pressure, lipid profile, ApoB, and ApoA levels. Data were statistically analyzed was using bivariate analysis and multivariate analysis. P-value <0.05 was statistically significant. The prevalence of PAD was 54.90%. Bivariate analysis of age variables (PR: 3.15; 95%Cl: 1.128-8.811; p=0.005), sdLDL (PR: 2; 95%Cl: 0.997-4.013; p=0.03), the ratio of ApoB/ApoA-I (PR: 5.786; 95%Cl: 0.899-37.224; p=0.007), and smoking (PR: 1.896; 95%Cl: 1.210-2.971; p=0.015) was significantly related with PAD. After adjustment of age, smoking, and dyslipidemia variables using multivariate logistic regression analysis, PAD was still related with sdLDL (PR: 10.55; 95%CI: 1.80-61.73; p=0.009), age (PR: 11. 61; 95%CI: 1.83-61.73; p=0.009), and smoking (PR: 11.96; 95%CI: 1.71-83.81; p= 0.013). sdLDL and ApoB/ApoA-I ratio were related to PAD. However, sdLDL, age, and smoking are independent variables of PAD in hypertension patients.